Towards authoritarianism. Internal situation in the Slovak Republic (1994-1998) - Żarna, Krzysztof (Przegląd Politologiczny, 2018)
This article discusses the internal situation of the Slovak Republic in the years 1994-1998, the period in which the country was governed by the coalition of Movement for Democratic Slovakia, the Slovak National Party and the Slovak Workers’ Association, and the prime minister was Vladimir Meciar. The main objective of the research was to analyse the actions undertaken by the coalition government in the context of violations of civil and political rights and freedoms, which could indicate an authoritarian way of exercising power and the dismantling of a democratic state of law. In the analysed period, the role of the parliamentary and nonparliamentary opposition was marginalised, the role of the media limited, the rights of national and ethnic minorities violated. There was also an ongoing, sharp conflict between Prime Minister Vladimir Meciar and President Michal Kovac. The effect of this governance was the union of almost all political forces and seizure of power after the elections in 1998. In order to answer the research questions, the author used the method of institutional and legal analysis, decision analysis and the statistical method. The research confirmed the hypothesis that, against the background of other Visegrad Group countries, the Czech Republic, Poland and Hungary, in the case of Slovakia there were many instances of human rights violations in the period analysed. This led to the drastic deterioration of bilateral relations with many countries and the slowdown of Slovakia’s accession to the North Atlantic Alliance and the European Union.